EFEKTIVITAS PELAKSANAAN PERATURAN GUBERNUR BALI NOMOR 41 TAHUN 2010 TENTANG STANDARISASI PENGELOLAAN DAYA TARIK WISATA BERKAITAN DENGAN PENGEMBANGAN OBYEK DAN DAYA TARIK WISATA DI KABUPATEN TABANAN - Triari Puri, Ni Nyoman; Markeling, I Ketut (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013)
Tabanan is rich in attractions, both natural attractions and cultural attractions all of which have high sales value if managed optimally. There are several things that must be considered in managing and developing objects and attractions, such provisions contained in Bali Governor Regulation Number 41 of 2010 on standardization management of a tourist attraction. This paper aims to answer the first two questions, what is the effectiveness of the implementation of the Bali governor regulation number. 41 of 2010 in Tabanan regency, and what factors influence the effectiveness of law in society. Legal research is empirical legal research using interview data collection techniques. Conclusions from the study showed that the number of attractions in the Tabanan regency which do not meet the management standards are still high tourist attraction. This is due to the factors that lead to less work in the law, the law / legislation, law enforcement, community facilities / amenities, and culture.
Keywords: Effectiveness, Standardization, Tourism Object, tourist attraction.